Soviet origins of the Kazakh press: national interests and political contradictions - Омашев, О.Н.; Saidirakhman, У. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2019)
The article outlines the problems of the Kazakh press in the 1920s. The main purpose of the article is to demonstrate that national intelligentsia has boldly criticized the land, language issues and openly protects the national interest. The article influences the Kazakh and foreign researchers to make a fresh statement of the Kazakh press’s mission of 1928. Because in Soviet times all the research was written on the basis of the Communist Party. Therefore, the Soviet authorities forbade the study of the heritage of Kazakh intelligentsia. They deleted the archives that exposed the truth. Therefore, it was very important to find and publish articles in the 1920s from secretly stored newspapers and magazines. It is also possible to expose the ionic pressure of the Soviet authorities to the people.